Brain Gray Matter Volume and Functional Connectivity Are Associated With Smoking Cessation Outcomes - Qian, Wei; Huang, Peiyu; Shen, Zhujing; Wang, Chao; Yang, Yihong; Zhang, Minming (Frontiers in Human Neuroscience, 2019)
Smoking cessation is critical for reducing the risk of respiratory, cardiovascular diseases and cancers. However, most cessation attempts resulted in failure. In the present study, we aim to explore whether alterations of brain gray matter (GM) volume and functional connectivity are related to cessation outcomes, in hope of providing evidence for improving smoking cessation outcomes. Seventy-three smokers and forty-one non-smokers were enrolled in the present study. All smokers participated in a 12-week smoking cessation treatment during which Varenicline was used to aid cessation. At the end of treatment, the smokers were divided into quitters and relapsers based on their abstinence performance. Structural magnetic resonance imaging and voxel-based morphometry were applied to quantify the differences of regional brain volumes among the three groups at baseline. In addition, resting-state functional connectivity was used to investigate the related functional changes. In comparison with nonsmokers, the smokers showed smaller GM volume in the left dorsal medial thalamus. Among the 73 smokers, 29 subjects successfully quitted smoking. The quitters showed greater GM volume than the relapsers in the right postcentral gyrus, right putamen\caudate nucleus and left orbitofrontal cortex. The GM volume in the left orbitofrontal cortex was found to be negatively correlated with the pack years and daily smoking amount in the quitters. Furthermore, we found significantly reduced functional connectivity between left thalamus and left cerebellum in the relapsers. These findings extended our knowledge of the neural mechanism of smoking cessation, and suggested that brain structural and functional changes were related to smoking cessation outcomes.